Spirituality Levels and Depression Levels on Elderly in Indonesia Local Health Center - Oktavianisya, N; Mulyadi, E; Ningsih, E Y (International Journal of Psychosocial Rehabilitation, 2020)
Elderly is the final stage of the human life cycle. Most elderly people feel that their condition live were not like their expectations, so this condition can triggers depression. The problem that occurs in the elderly at the Tejaya Health Centre is the unpreparedness of the elderly in facing retirement, most of them are not noticed by their families. This study aims to determine the relationship between the level of spirituality and the level of depression in the elderly at the Teja Public Health Centre in Pamekasan Regency. The research design used analytic, with Cross-Sectional design. The method used gathering primary and secondary data by interview using a questionnaire. The sample in this study used the elderly in the Teja Pamekasan Health Centre Pamekasan Regency as many as 60 people. The results showed that respondents who experienced mild depression (25.0%) and high spirituality (41.7%). Statistical test results with the Spearman correlation test showed p-values was smaller than α (0.01